ACTIVITY-BASED COSTING AND THROUGHPUT ACCOUNTING OF TOC: A HYBRID SYSTEM IN THE MANAGERIAL ACCOUNTING - Alves, João Murta; Santos, Reinaldo Fagundes dos (Revista Ciências Exatas, 2023)
The Throughput Accounting (TA), based on the Theory of Constraints (TOC), has as goal to supply managerial information to find bottlenecks generated by resource constraints, so that the same ones can be explored and later high, increasing the gains of the organization. Goldratt affirms that any system has at least one constraint that limits the company in the attempt of reaching its goals. The Activity-Based Costing (ABC) has as basis the tracing of activities that consuming resources and allocation of the same ones in the products. This trace is made through the processes mapping, which can also help in the identification of bottlenecks, generating causes and eventual forms of reducing them or even to eliminate them. This article analyzes as antagonistic systems like ABC that has focus in the product’s cost and TA that the goal is to maximize the product’s gains, can be complemented and be used for generation of a robust costing system and to leave available coherent and useful information for managerial decisions. This comparative analysis evidences that the decisions based on hybrid systems are more efficient. A case study is presented, in that the use of the Throughput Accounting (TA), as managerial tool, supported by Activity-Based Costing (ABC) took the investigated company to improve its results.